Accesses of Short Story Texts- A Narrative study in Collection of " A Man in Fly's Brain" by Ala' Shakir (Journal of the College of Basic Education, 2026)
The short story remains a sophisticated art form that maintains a prominent status among other narrative genres. Over the years, it has flourished in richness and diversity, shaped by eminent figures who have secured a distinguished place in its history. Among these figures is the writer Alaa Shaker, born in Basra—a pioneering city of arts and sciences that previously birthed the master of the short story, Mohammed Khudayr.​Upon analyzing Alaa Shaker’s texts, it becomes evident that he possesses a profound mastery of the narrative craft, showcasing a technical superiority in this genre. This study of his collection, A Man in a Fly's Mind, adopts a constructive-descriptive approach. It examines the elements of narrative structure—Time, Space, Narration, and Visionary Construction—and their interrelationships across three distinct levels for each element. We have endeavored to uncover the literariness of his texts and their inherent aesthetic and artistic objectives.​In Alaa Shaker's work, the narrative text is a structure that continuously reshapes itself. The author skillfully crafts his narrative system to consistently provoke inquiry. For him, structure is an aesthetic framework that embeds the seeds of communication with the "Other" through an enlightened synergy between time, space, character, and vision. The "narrative birth" in his stories is never a finished state; rather, it remains in a constant flux of energy, fueled by a sensory pulse that keeps the text's flame ignited—a quality we may term the "Spirituality of the Narrative Text." The text here is a living entity, capable of seducing the reader. While the author acts as a monitor and guide, he does so through technical mastery rather than direct presence, encoding the narrative system so that he controls the "strings of the game." Meanwhile, the reader is tasked with finding the keys to activate this system, creating an aesthetic pleasure that links the author, the text, and the reader within an open communicative space. In the following pages of this research, we shall delve deeper into this analytical reading